Proposição de um método de dosagem racional de concretos de ultra-alto desempenho - Maia, Alessandra Tourinho (2021)
This research aimed to propose a rational method for dosing ultra-high performance concretes based on the association of three approaches: the definition of the ideal silica content, the use of the minimum paste volume and the incorporation of fine basalt artificial sand. Through the combination of experimental methods and granular packing models, a robust experimental program consisting of eight steps was developed, aiming to obtain different compositions of ultra-high performance concretes, with selfcompacting characteristics and compressive strength greater than 150 MPa at 28 days, after heat water treatment at 90°C. In addition, the influence of silica content, additional paste volume, different types of cure, test ages and the addition of metallic fibers on the fluidity and strength of the composites were evaluated.Through the proposed method, the average strength of 186 MPa was achieved in the mix containing the minimum volume of paste, 484 kg∕m³ of cement and 25% of silica fume. The results obtained indicate that the proposed method tends to have the best proportion among the component materials, giving rise to traits that fit the international parameters that define the UHPC, but with reduced paste volumes and consumption of binders lower than those identified in the related literature. Through a rational, economic and sustainable approach, which aims to optimize the use of higher cost materials and minimize the use of scarce natural resources, the method contributes positively to the technological development of the sector.